A construção de representações coletivas: a semiótica no estudo do patrimônio público em Chapecó/SC - Dalla Zen, Daniel (2019)
This research has the goal of understanding the relationship between the colonization and the construction of collective representations through the study of public property inaugurated on the anniversaries of the city of Chapecó/SC. It is understood that, having been built by representatives of the municipal public power, it is attributed to these properties an official character. Therefore, the problematization involves the interrogation of how the city presents and represents the history of its colonization, emphasizing certain images, on the places and periods in which they are inaugurated. The methodology used in this study involves bibliographic research based on authors who study the colonization of Western Santa Catarina. It also includes documental research referring to the public patrimonies of the city of Chapecó/SC. In dialogue with the references, there were selected and analyzed through semiotic, the three properties inaugurated on the anniversaries of the city: Monumento O Desbravador (1981), Mural O Ciclo da Madeira (2001), and Monumento 100 Anos de Chapecó (2017). The study of this monuments in dialogue with the bibliographical and documental research, allows the statement that the plurality of representations regarding the colonization in Chapecó/SC, originating on the different groups: indigenous caboclos and colonists are faded, while the official narrative of a homogeneous representation highlights and reinforces an unilateral dimension, prioritizing the narrative of the colonizer as a pioneer, discovering the region.